Examples of Distorted Interval Diffeomorphisms of Intermediate Regularity - Dinamarca-Opazo, L; Escayola-Acosta, M (Cambridge University Press, 2022)
We improve a recent construction of Andrés Navas to produce the first examples of C2-undistorted diffeomorphisms of the interval that are C1+α-distorted (for every α < 1). We do this via explicit computations due to the failure of an extension to class C1+α of a classical lemma related to the work of Nancy Kopell. © The Author(s), 2021. Published by Cambridge University Press.